Determining Visitors’ Intention to Revisit Surabaya Mangrove Forest - Syarif, Mochamad (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The background of this study is visitors who show intention to visit again. In this case, visitor intention is something that needs to be considered for the decisions that visitors must make in the future. The objectives of this study are: (1) to determine visitor intentions, (2) to determine visitor satisfaction, (3) so that visitors want to visit Surabaya mangrove forest again. Data was obtained by conducting interviews with visitors who were at the Surabaya mangrove forest location. This method was chosen because the investigation aims to describe visitors who are visiting the Surabaya mangrove forest. In addition, it is presented in a good format for easy reading. The data is then analyzed and conclusions are drawn.